The Theory of Planned Behavior & Bystander Intention: Differences Based on Gender and Heavy Episodic Drinking - John, Dylan A. (Journal of interpersonal violence, 2022)
Research indicates that people who engage in heavy episodic drinking (HED) report less intention to intervene and intervention behavior to prevent sexual violence. Researchers have also found gender differences across bystander intention, bystander confidence, and intervention behavior. However, research in this area could benefit from use of an evidence-based health behavior theory. The theory of planned behavior (TPB) posits that personal attitudes, subjective norms, and perceived behavioral control (PBC) predict behavioral intention. Substantial evidence supports the utility of the TPB for predicting behavioral intention in a variety of health-related behaviors, yet few researchers have applied this theory when predicting bystander intention to prevent sexual violence. Undergraduate students (N = 395) from a southern university (77% female; 70% White, Non-Hispanic) completed a modified Sexual Assault Bystander Behavior Questionnaire and the Daily Drinking Questionnaire. Our findings did not reveal significant differences in attitudes, subjective norms, PBC, nor intention based on HED; however, there were significant differences based on gender, with women indicating more positive attitudes and supportive subjective norms regarding bystander intervention. Multiple regression analysis indicated that theoretical antecedents of intention positively predicted bystander intention, however, the relations were not moderated by prior engagement in HED. These findings support the utility of the TPB for predicting bystander intention to intervene; however, they do not support previous research examining how HED influences bystanders? intention to engage in prosocial actions.